Personalmanagement in der Logistikwirtschaft - Florian Bovie; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2007)
– This paper deals with the question of general developments in logistics services. These trends influence the question of human resource management in the logistics service industry as well as the general demographic trend of a declining population in Germany and Europe. Thus the authors show some options for companies to react on shortenings in employee supply - but all in all trends as e.g. higher qualification requirements and work time regulations have an overwhelming impact. This highlights the future problems of HR management in logistics even more and may pose a real bottleneck situation for the thriving logistics industry.
Keywords: 650; Personalmanagement; Logistikunternehmen